Effectiveness of Revolutic Biospray Preparations Against Wound Healing - Naomi Malaha; Dewi Sartika; Rahmat Pannyiwi; Zainal; Via Zakiah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The skin has a major function in protecting the body from environmental influences. If it is injured, it will interfere with activities, cause pain, and facilitate infection. Furthermore, if this wound is wide and deep, it will be difficult to heal. Wound healing essential for the restoration of severed tissue, in this case, the skin, both anatomically and functionally. Damaged tissue will start the wound healing process, which is replacing damaged tissue or necrotic tissue with new and healthy tissue. Based on this explanation, the researcher interested in studying the role of Topical Biospray by Nutric on the number of PMN Leukocytes (neutrophils), Macrophages, Fibroblasts, Epithelialization, Cytokines Transforming Growth Factor – beta (TGF – β), and Wound Diameter in accelerating the wound healing process. This research was conducted at the Animal Laboratory of the Faculty of Medicine Hasanudin University, the Anatomy and Physiology Lab of Hasanuddin University, and the RSP Lab of Hasanudin University, applying the Randomized Post Test Control Group research design, using Wistar rats as research subject which were divided into 3 groups with different conditions and conditions. Revolutic Biospray applied topically to Wistar's wound. From the research conducted, it is proven that the relationship between wound healing using Biospray Revolutic compared to 0.9% NaCl solution and Biospray Plus preparations can provide very significant results at the stages of wound healing in the inflammatory, proliferative and maturation phases.